Extraction optimization of phenolic compound from Zingiber aromaticum rhizome using pressurized hot water extraction - Asma' Hannani Ahmad Daud (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Pressurized hot water extraction (PHWE) method was implemented in order to reduce the usage of organic solvent in extracting phenolic compound from the rhizome of Zingiber aromaticum. At first, the screening studies using single factorial experiments were performed prior to optimization. The range of the independent variables, namely as extraction temperature (60-150 C), extraction time (10-50 minutes) and particle size of plant sample (63-750 (So(Bm) were determined, then the values of independent variables were selected for optimization. Next, the optimum conditions of the process parameters were determined by employing Response Surface Methodology (RSM) in conjunction with central composite design (CCD). The effects of extraction temperature, time and particle size towards total phenolic content (TPC) were investigated. Results showed that the extraction temperature was significant factor affecting on the TPC. It was predicted that the optimum extraction condition would be the temperature of 160 C, extraction time of 45 min and particle size of 599.67 (So(Bm. Under the optimized condition, the highest value of TPC obtained was 7.078 mg GAE/g dry weight which reasonably close to the predicted value of 7.098 mg GAE/g dry weight. Thus, the results showed that the second order polynomial model was significant since the data were adequately fitted into the model.